A tremella-like sodium iron phosphate pyrophosphate composite material and its preparation method and application

By preparing a Tremella-like sodium iron pyrophosphate composite material in Na4Fe3(PO4)2P2O7 cathode material, embedded in a three-dimensional sheet-like rGO material and adding metal nanocrystals, the existing material has solved the problem of poor endurance and high current density. The problem of poor rate performance has achieved high-efficiency sodium-ion battery cathode material performance.

CN118929615BActive Publication Date: 2025-01-24SHANDONG HAIHUA GRP CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411411590.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-24
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing Na4Fe3(PO4)2P2O7 positive electrode material has poor bearing capacity at high current density, low capacity release rate, and poor rate performance, which cannot meet the needs of sodium ion batteries.

Method used

Using sodium -like sodium -like iron phosphate composite material, prepare NA4FE3 (PO4) 2P2O7 spherical material through spray drying and water heating reactions, and inlaid them in a three -dimensional sheet -shaped RGO material. Increase conductivity and cycle stability.

Benefits of technology

Significantly improved the reaction kinetics and rate performance of Na4Fe3(PO4)2P2O7, releasing a high capacity of 77.09mAhg-1 at a high current density of 50C, and maintaining a capacity of 83.56mAhg-1 after 2100 cycles, with a cycle decay rate Low, the Coulomb efficiency is as high as 99.97%, and the retention rate is 93.12%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118929615B_ABST
    Figure CN118929615B_ABST
Patent Text Reader

Abstract

The invention discloses a tremella-like sodium iron phosphate pyrophosphate composite material and a preparation method and application thereof, belonging to the technical field of sodium ion battery positive electrode materials. An inorganic salt containing sodium and phosphorus, a chain carbon source and an inorganic strong acid iron salt are mixed and reacted and spray-dried to obtain a Na4Fe3(PO4)2P2O7 material precursor; GO is then added for mixed reaction to form a Na4Fe3(PO4)2P2O7 precursor / GO mixed solution; a hydrothermal reaction is then performed to load an inorganic strong acid zinc salt or an inorganic strong acid cobalt salt, and calcined in an Ar-H2 atmosphere to obtain a tremella-like sodium iron phosphate pyrophosphate composite material. The composite material has good electrical conductivity and cycle stability and is suitable for sodium ion batteries. At a high current density of 50C, 77.09mAhg can still be released. ‑1 At 1C current density, it can still release 83.56 mAh g after 2100 cycles. ‑1 The cycle attenuation rate is as low as 0.003%, the Coulomb efficiency is as high as 99.97%, and the retention rate is 93.12%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and particularly relates to a tremella-like sodium iron phosphate pyrophosphate composite material, a preparation method and an application thereof. Background Art

[0002] Global lithium resources are limited and unevenly distributed. my country's lithium resources typically exist in co-existing forms, making lithium extraction and purification from salt lakes challenging. However, my country's power battery and energy storage markets are growing rapidly, and limited lithium resources are becoming a constraint to their development. Therefore, it is imperative to seek energy storage resources with abundant reserves that can meet market demand.

[0003] The limited availability of lithium resources and the surge in demand have triggered significant price fluctuations for lithium carbonate, drawing the attention of battery companies. Since 2023, sodium-ion batteries have entered their first year of development, and their industrialization has continued to advance. However, the cathode routes for sodium-ion batteries are diverse and undergoing continuous improvement.

[0004] The theoretical specific capacity of Na4Fe3(PO4)2P2O7 is 129mAhg -1 The operating voltage is 3.2V and it requires sodium carbonate, iron salts, and a phosphorus source as raw materials. It has the advantages of being environmentally friendly, low cost, and good cycle stability. However, Na4Fe3(PO4)2P2O7 has low conductivity, low capacity release rate, and poor rate performance, which cannot meet the requirements in the application process.

[0005] The Chinese patent document with publication number CN107069012A discloses a hollow spherical Na4Fe3(PO4)2P2O7 / composite cathode material and its preparation method. A surfactant is introduced to form spherical Na4Fe3(PO4)2P2O7 using an emulsion soft film method. The carbon source (one or more of starch, citric acid, sucrose, glucose, and phenolic resin) and surfactant introduced during the material preparation process are converted into a conductive carbon material after calcination to finally form a hollow spherical Na4Fe3(PO4)2P2O7 / C composite material with a maximum current density of 200mAg. -1 , the initial capacity is 66mAhg -1 The capacity retention rate after 500 cycles is 68%. The problems are that the ability to withstand large currents is poor, the specific capacity release rate is low, and the retention rate is poor. Summary of the Invention

[0006] The present invention aims to provide a tremella-like sodium iron phosphate pyrophosphate composite material, a preparation method and application thereof; the prepared tremella-like sodium iron phosphate pyrophosphate composite material has good electrical conductivity and cycle stability, and is suitable for sodium ion batteries.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a Tremella-like sodium iron phosphate pyrophosphate composite material, comprising the following steps:

[0009] (1) Dissolve an inorganic salt containing sodium and phosphorus, a chain carbon source, and an inorganic strong acid iron salt in deionized water and stir to react, and spray-dry the reaction solution to obtain a Na4Fe3(PO4)2P2O7 material precursor;

[0010] (2) Adding Na4Fe3(PO4)2P2O7 material precursor and GO into deionized water, ultrasonically dispersing to form a Na4Fe3(PO4)2P2O7 precursor / GO mixed solution; performing a hydrothermal reaction to obtain a Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution;

[0011] (3) Adding an inorganic strong acid zinc salt or an inorganic strong acid cobalt salt to the Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution, stirring evenly to form a suspension, filtering, washing, and drying the suspension to obtain a composite material precursor; calcining the composite material precursor in an Ar-H2 atmosphere to obtain a Tremella-like sodium iron phosphate pyrophosphate composite material (Na4Fe3(PO4)2P2O7 / rGO / M).

[0012] Furthermore, in the step (1), the inorganic salt containing sodium and phosphorus is sodium hypophosphite or sodium dihydrogen phosphate; the inorganic strong acid iron salt is ferric nitrate or ferric chloride; the chain carbon source is glucose or citric acid; the molar ratio of the inorganic salt containing sodium and phosphorus, the inorganic strong acid iron salt, and the chain carbon source is 0.4 mol: 0.29-0.31 mol: 0.03-0.05 mol; the spray drying temperature is 110-150°C; and the flow rate is 200-300 mL / h. -1 .

[0013] Furthermore, in the step (2), the mass ratio of the added Na4Fe3(PO4)2P2O7 material precursor to GO is 10-20:1; the hydrothermal reaction temperature is 150-180°C; and the hydrothermal reaction is carried out for 15-24 hours.

[0014] Furthermore, in the step (3), the added inorganic strong acid zinc salt is zinc chloride or zinc nitrate; the inorganic strong acid cobalt salt is cobalt chloride or cobalt nitrate; the mass volume ratio of the inorganic strong acid zinc salt or inorganic strong acid cobalt salt and the Na4Fe3(PO4)2P2O7 / rGO mixed solution is 10~50mg:30mL; the stirring time is 3~7h; the calcination process is first heating to 300~350℃ and keeping warm for 1~3h; then heating to 550~600℃ and keeping warm for 8~10h.

[0015] In a second aspect, the present invention provides a Tremella-like sodium iron phosphate pyrophosphate composite material prepared by the above method.

[0016] In a third aspect, the present invention also provides the use of the Tremella-like sodium iron phosphate pyrophosphate composite material prepared by the above method in sodium ion batteries.

[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0018] 1. The tremella-like sodium iron phosphate pyrophosphate composite material provided by the technical solution of the present invention includes a three-dimensional sheet-like rGO material and a Na4Fe3(PO4)2P2O7 spherical material, wherein the diameter of the Na4Fe3(PO4)2P2O7 spherical material is 2 to 6 microns; the Na4Fe3(PO4)2P2O7 spherical material is embedded in the three-dimensional sheet-like rGO material to form a tremella-like three-dimensional composite structure;

[0019] The surface of the three-dimensional sheet rGO material is also uniformly loaded with zinc or cobalt metal nanocrystals; the Na4Fe3(PO4)2P2O7 spherical material is a micron-sized material formed by the accumulation of nanoparticles. Compared with the existing technology, it not only improves the structural stability of the material, but also facilitates electrolyte infiltration and ion shuttling, accelerating the kinetic reaction.

[0020] The spherical Na4Fe3(PO4)2P2O7 material is embedded in the three-dimensional sheet-like rGO material to form a Tremella-like three-dimensional composite structure. Compared with carbon coating and carbon doping, the Tremella-like three-dimensional composite structure connects multiple spherical precursors, providing more pathways for ion and electron transfer at the interfaces of different spheres. It also has a certain volume-limiting effect on the embedded spheres, which is more conducive to maintaining the stability of the positive electrode material structure and further improving the cycle stability of sodium-ion batteries.

[0021] Electrons on rGO are transferred along carbon chains. After loading with zinc or cobalt metal nanocrystals, conductive sub-paths are formed where the carbon chains and metal nanocrystals intersect. Electrons are then transported along the path with the lowest resistance within this intersecting conductive network, significantly reducing electron transfer resistance. Compared to carbon-source-modified materials, the metal nanocrystals used in this invention have higher conductivity and better dispersion, significantly improving the conductivity of the conductive network.

[0022] The technical solution of the present invention uses ultrasound to highly evenly disperse the Na4Fe3(PO4)2P2O7 spherical precursor and GO in water, and reduces GO to rGO through a hydrothermal reaction, ultimately forming a tremella-like three-dimensional composite structure in which Na4Fe3(PO4)2P2O7 spherical materials are embedded in a three-dimensional flaky rGO material, thereby improving the stability of the positive electrode material structure and thereby improving the cycle stability of the sodium ion battery.

[0023] The technical solution of the present invention is to add zinc salt or cobalt salt to the Na4Fe3(PO4)2P2O7 / rGO mixed solution. After the metal salt is dissolved, it is evenly dispersed on the Na4Fe3(PO4)2P2O7 / rGO material. During the high-temperature calcination process, the metal salt is converted into metal nanocrystals through carbon reduction; the metal nanocrystals are evenly deposited on the rGO to form a three-dimensional thin film framework; compared with a single carbon material, not only the amount of carbon introduced is reduced, but also the conductivity of the conductive network is improved.

[0024] The technical solution of the present invention uses spray drying to prepare the Na4Fe3(PO4)2P2O7 precursor. If the flow rate is too fast, the spray droplets will be large, requiring a higher temperature to dry them and increasing energy consumption. However, if the drying temperature is not reached, the nozzle will be clogged. If the flow rate is too slow, the material preparation efficiency is low. Therefore, a matching temperature and flow rate are required to carry out the spray drying process. By controlling the flow rate and temperature, the present invention can make the precursor particle size distribution between 2 and 6 microns. Na4Fe3(PO4)2P2O7 / rGO is calcined in an Ar-H2 mixed atmosphere. The hydrogen reducing atmosphere can avoid the iron ions from having multiple valence states, thereby ensuring the purity and specific capacity of the target material.

[0025] 2. The technical solution of the present invention effectively improves the reaction kinetics of Na4Fe3(PO4)2P2O7 and optimizes the rate performance of Na4Fe3(PO4)2P2O7. At a high current density of 50C, it can still release 77.09mAhg -1 At a current density of 1C, it can still release 83.56 mAh g after 2100 cycles. -1 The cycle attenuation rate is as low as 0.003%, the Coulomb efficiency is as high as 99.97%, and the retention rate is 93.12%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM morphology image of the Na4Fe3(PO4)2P2O7 precursor obtained in Example 1 at an electron microscope magnification of 1540 times;

[0027] Figure 2 This is a SEM morphology of the Tremella-like sodium iron phosphate pyrophosphate composite material (Na4Fe3(PO4)2P2O7 / rGO / Zn) obtained in Example 1 at an electron microscope magnification of 3860 times;

[0028] Figure 3 This is a SEM morphology of the Tremella-like sodium iron phosphate pyrophosphate composite material (Na4Fe3(PO4)2P2O7 / rGO / Zn) obtained in Example 1 at an electron microscope magnification of 5060 times;

[0029] Figure 4This is the XRD diffraction pattern of the Tremella-like sodium iron phosphate pyrophosphate composite material (Na4Fe3(PO4)2P2O7 / rGO / Zn) obtained in Example 1;

[0030] Figure 5 This is a graph showing the rate performance of the Tremella-like sodium iron phosphate pyrophosphate composite material (Na4Fe3(PO4)2P2O7 / rGO / Zn) obtained in Example 1 as a positive electrode material in a sodium ion battery at different current densities;

[0031] Figure 6 This is a long cycle diagram of the Tremella-like sodium iron phosphate pyrophosphate composite material (Na4Fe3(PO4)2P2O7 / rGO / Zn) obtained in Example 1 used as a positive electrode material in a sodium ion battery at a current density of 1C. DETAILED DESCRIPTION

[0032] The present invention will be further described in detail below with reference to the following examples. The accompanying drawings and examples are only used to illustrate the present invention and do not constitute an improper limitation of the present invention. Example 1

[0033] (1) Add 0.4 mol sodium dihydrogen phosphate, 0.3 mol ferric nitrate, and 0.05 mol citric acid into 500 mL deionized water and stir to react. -1 The precursor of Na4Fe3(PO4)2P2O7 material was obtained by spray drying under the following conditions;

[0034] (2) 0.2 g Na4Fe3(PO4)2P2O7 material precursor and 10 mg GO were added to 30 mL deionized water and ultrasonically dispersed for 30 min to form a Na4Fe3(PO4)2P2O7 precursor / GO mixed solution, which was then transferred to a reactor and reacted at 160 °C for 24 h to obtain a Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution;

[0035] (3) The Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution was transferred to a beaker, 50 mg of zinc nitrate was added thereto and stirred for 5 h. The suspension was evenly stirred to form a suspension, which was filtered, washed and dried to obtain a composite material precursor; the composite material precursor was calcined in an Ar-H2 atmosphere, first at 300 °C for 1 h, and then heated to 550 °C for 10 h to obtain a Tremella-like sodium iron phosphate pyrophosphate composite material (Na4Fe3(PO4)2P2O7 / rGO / Zn).

[0036] The Na4Fe3(PO4)2P2O7 precursor obtained in Example 1 was observed using a scanning electron microscope. Figure 1As shown, the precursor is a spherical material with a particle size distribution of 2~6μm. The material finally obtained in Example 1 was observed. The spherical material Na4Fe3(PO4)2P2O7 was embedded in the three-dimensional sheet-like rGO material to form a three-dimensional composite structure similar to Tremella fuciformis. Compared with carbon coating and carbon doping, the three-dimensional composite structure similar to Tremella fuciformis connects multiple spherical precursor individuals, and there are more paths for transferring ions and electrons at different spherical interfaces. And there is a certain volume limiting effect on the spheres embedded therein, which is more conducive to maintaining the stability of the positive electrode material structure and further improving the cycle stability of the sodium ion battery. The electrons on rGO are transferred along the carbon chain. After loading the metal nanocrystals, a conductive sub-path is formed in which the carbon chain and the metal nanocrystals intersect with each other, and the electrons are transmitted along the transfer path with the least resistance in the cross-conductive network path. The present invention introduces metal nanocrystals with higher conductivity and good dispersion uniformity. The metal nanocrystals and the carbon source cooperate with each other to provide a conductive network with higher conductivity, such as Figure 2 and Figure 3 The powder finally obtained in this embodiment was subjected to XRD diffraction test, and the results are shown as follows: Figure 4 Synthesis of the shown supporting materials. Example 2

[0037] (1) Add 0.4 mol sodium dihydrogen phosphate, 0.29 mol ferric chloride, and 0.05 mol citric acid into 500 mL deionized water and stir to react. -1 The precursor of Na4Fe3(PO4)2P2O7 material was obtained by spray drying under the following conditions;

[0038] (2) 0.3 g Na4Fe3(PO4)2P2O7 material precursor and 30 mg GO were added to 30 mL deionized water and ultrasonically dispersed for 30 min to form a Na4Fe3(PO4)2P2O7 precursor / GO mixed solution, which was then transferred to a reactor and reacted at 150 °C for 15 h to finally obtain a Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution;

[0039] (3) The Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution was transferred to a beaker, 50 mg of cobalt nitrate was added thereto and stirred for 7 h. The suspension was evenly stirred to form a suspension, which was filtered, washed and dried to obtain a composite material precursor; the composite material precursor was calcined in an Ar-H2 atmosphere, first at 350 °C for 3 h, and then heated to 550 °C for 8 h to obtain a Tremella-like sodium iron phosphate pyrophosphate composite material (Na4Fe3(PO4)2P2O7 / rGO / Co). Example 3

[0040] (1) Add 0.4 mol sodium hypophosphite, 0.31 mol ferric nitrate and 0.03 mol glucose into 500 mL deionized water and stir to react. -1 The precursor of Na4Fe3(PO4)2P2O7 material was obtained by spray drying under the following conditions;

[0041] (2) 0.5 g Na4Fe3(PO4)2P2O7 material precursor and 50 mg GO were added to 30 mL deionized water and ultrasonically dispersed for 30 min to form a Na4Fe3(PO4)2P2O7 precursor / GO mixed solution, which was then transferred to a reactor and reacted at 180 °C for 20 h to finally obtain a Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution;

[0042] (3) The Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution was transferred to a beaker, 30 mg of zinc chloride was added thereto and stirred for 3 h, then filtered, washed and dried to obtain a composite material precursor; the composite material precursor was calcined in an Ar-H2 atmosphere, first at 300 °C for 1 h, then heated to 550 °C for 8 h, and finally a Tremella-like sodium iron phosphate pyrophosphate composite material (Na4Fe3(PO4)2P2O7 / rGO / Zn) was obtained. Example 4

[0043] (1) Add 0.4 mol sodium dihydrogen phosphate, 0.3 mol ferric nitrate, and 0.05 mol citric acid into 500 mL deionized water and stir to react. -1 The precursor of Na4Fe3(PO4)2P2O7 material was obtained by spray drying under the following conditions;

[0044] (2) 0.2 g Na4Fe3(PO4)2P2O7 material precursor and 10 mg GO were added to 30 mL deionized water and ultrasonically dispersed for 30 min to form a Na4Fe3(PO4)2P2O7 precursor / GO mixed solution, which was then transferred to a reactor and reacted at 160 °C for 24 h to finally obtain a Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution;

[0045] (3) The Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution was transferred to a beaker, 50 mg of cobalt chloride was added thereto and stirred for 5 h, then stirred evenly to form a suspension, which was filtered, washed, and dried to obtain a composite material precursor; the composite material precursor was calcined in an Ar-H2 atmosphere, first at 300 °C for 1 h, then heated to 600 °C for 10 h, and finally a Tremella-like sodium iron phosphate pyrophosphate composite material (Na4Fe3(PO4)2P2O7 / rGO / Co) was obtained. Comparative Example

[0046] (1) Add 0.4 mol sodium dihydrogen phosphate, 0.3 mol ferric nitrate, and 0.05 mol citric acid into 500 mL deionized water and stir to react. -1 The precursor of Na4Fe3(PO4)2P2O7 material was obtained by spray drying under the following conditions;

[0047] (2) 0.2 g Na4Fe3(PO4)2P2O7 material precursor and 10 mg GO were added to 30 mL deionized water and ultrasonically dispersed for 30 min to form a Na4Fe3(PO4)2P2O7 precursor / GO mixed solution, which was then transferred to a reactor and reacted at 160 °C for 24 h to obtain a suspension, which was then filtered, washed, and dried to obtain a composite material precursor; the composite material precursor was calcined in an Ar-H2 atmosphere, first at 300 °C for 1 h, then heated to 550 °C for 10 h, and finally a Tremella-like sodium iron phosphate pyrophosphate composite material (Na4Fe3(PO4)2P2O7 / rGO) was obtained.

[0048]

[0049] The materials prepared in the examples and comparative examples were used as positive electrodes in sodium ion batteries. From the data in Table 1, it can be seen that the electrochemical performance of the material obtained in Example 1 is the best, proving that this condition is the best. The specific capacity released by the composite materials obtained in Examples 1 and 3 loaded with Zn metal nanocrystals is higher than that of the composite materials obtained in Examples 2 and 4 loaded with Co metal nanocrystals, proving that Zn nanocrystals and rGO synergistically improve conductivity. The electrochemical performance of the material in the comparative example without loading metal nanocrystals is the worst, proving that the loading of metal nanocrystals is effective. The material structure designed in this patent effectively improves the conductivity of the material, accelerates the reaction kinetics, and exhibits the following performance: Figure 5 The excellent rate performance shown in the figure can still release 77.09 mAh g at a current density of up to 50C. -1 The Tremella-like structure can better maintain the structural stability of the material. The test results at 1C current density are as follows. Figure 6 As shown, the first cycle discharge capacity is 89.73mAhg -1 After 2100 cycles, it can still release 83.56 mAh g -1 The cycle attenuation rate is as low as 0.003%, the Coulomb efficiency is as high as 99.97%, and the retention rate is 93.12%.

Claims

1. A method for preparing a Tremella-like sodium iron phosphate pyrophosphate composite material, characterized in that: The steps include: (1) dissolving an inorganic salt containing sodium and phosphorus, a chain carbon source and an inorganic strong acid iron salt in deionized water and stirring the mixture for reaction, and spray drying the reaction solution to obtain a Na4Fe3(PO4)2P2O7 material precursor; (2) adding Na4Fe3(PO4)2P2O7 material precursor and GO into deionized water, and ultrasonically dispersing them to form a Na4Fe3(PO4)2P2O7 precursor / GO mixed solution; and performing a hydrothermal reaction to obtain a Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution; (3) Adding an inorganic strong acid zinc salt or an inorganic strong acid cobalt salt to the Na4Fe3(PO4)2P2O7 precursor / rGO mixed solution, stirring the suspension to form a suspension, filtering, washing, and drying the suspension to obtain a composite material precursor; calcining the composite material precursor in an Ar-H2 atmosphere to obtain a Tremella-like sodium iron phosphate pyrophosphate composite material.

2. The method for preparing the Tremella-like sodium iron phosphate pyrophosphate composite material according to claim 1, wherein: In the step (1), the inorganic salt containing sodium and phosphorus is sodium hypophosphite or sodium dihydrogen phosphate; the inorganic strong acid iron salt is ferric nitrate or ferric chloride; the chain carbon source is glucose or citric acid; the molar ratio of the inorganic salt containing sodium and phosphorus, the inorganic strong acid iron salt, and the chain carbon source is 0.4 mol: 0.29-0.31 mol: 0.03-0.05 mol; the spray drying temperature is 110-150°C; and the flow rate is 200-300 mL / h -1 .

3. The method for preparing the Tremella-like sodium iron phosphate pyrophosphate composite material according to claim 1, wherein: In the step (2), the mass ratio of Na4Fe3(PO4)2P2O7 material precursor to GO is 10-20:1; the hydrothermal reaction temperature is 150-180°C; and the hydrothermal reaction time is 15-24h.

4. The method for preparing the Tremella-like sodium iron phosphate pyrophosphate composite material according to claim 1, wherein: In the step (3), the inorganic strong acid zinc salt is zinc chloride or zinc nitrate; the inorganic strong acid cobalt salt is cobalt chloride or cobalt nitrate; the mass volume ratio of the inorganic strong acid zinc salt or inorganic strong acid cobalt salt and the Na4Fe3(PO4)2P2O7 / rGO mixed solution is 30-50 mg:30 mL; the stirring time is 3-7 h; the calcination process is firstly heating to 300-350°C and keeping warm for 1-3 h; then heating to 550-600°C and keeping warm for 8-10 h.

5. A tremella-like sodium iron phosphate pyrophosphate composite material prepared by the method according to any one of claims 1 to 4.

6. Use of the tremella-like sodium iron phosphate pyrophosphate composite material as claimed in claim 5 in a sodium ion battery.

Citation Information

Patent Citations

  • Hollow spherical Na<4>Fe<3>(PO<4>)<2>P<2>O<7> / C composite positive electrode material and preparation method therefor

    CN107069012A

  • RGO-alpha-Fe2O3 / ZnFe2O4 composite material as well as preparation method and application thereof

    CN117783221A

  • Composite ferric sodium pyrophosphate material and preparation method thereof

    CN117945377A